The influence of resveratrol adaptation on resistance to antibiotics, benzalkonium chloride, heat and acid stresses of Staphylococcus aureus and Listeria monocytogenes - Oliveira, Adriana R. (2020)
Natural products have been presented as possible food preservatives due to their antimicrobial properties with some of these already being used in the food industry. However, it is known that microorganisms are able to adapt to antimicrobial agents, even if from natural sources, and some stresses. In this study, the influence of subinhibitory concentrations of resveratrol on Staphylococcus aureus ATCC 25923 and Listeria monocytogenes LMG 16779 was studied by evaluating the development of homologous- or cross-resistance to the antibiotics (ampicillin, erythromycin, vancomycin) commonly used to treat infections caused by these bacteria, as well as to one disinfectant (benzalkonium chloride) often used in the food sector. The development of tolerance against adverse conditions, acid (pH 2.4) and heat (55 °C) stresses, after the bacterial adaptation to resveratrol (¼ and ½ × MIC) was also assessed. The results suggest that resveratrol does not lead to homologous- or cross-resistance development for both strains studied, nonetheless it was observed a significant increase in tolerance to acid and heat stress in the case of L. monocytogenes and heat stress for S. aureus. These results, thus, indicate that resveratrol has potential to be used as a food preservative depending on the food processing conditions.